Antagonistic Regulation of Growth and Immunity by the Arabidopsis Basic Helix-Loop-Helix Transcription Factor HOMOLOG OF BRASSINOSTEROID ENHANCED EXPRESSION2 INTERACTING WITH INCREASED LEAF INCLINATION1 BINDING bHLH1 . Issue 3 (17th January 2014) - Malinovsky, Frederikke Gro; Batoux, Martine; Schwessinger, Benjamin; Youn, Ji Hyun; Stransfeld, Lena; Win, Joe; Kim, Seong-Ki; Zipfel, Cyril
Abstract : A basic helix-loop-helix transcription factor antagonistically regulates growth and immunity . Abstract: Plants need to finely balance resources allocated to growth and immunity to achieve optimal fitness. A tradeoff between pathogen-associated molecular pattern (PAMP )-triggered immunity (PTI ) and brassinosteroid (BR )-mediated growth was recently reported, but more information about the underlying mechanisms is needed. Here, we identify the basic helix-loop-helix (bHLH ) transcription factor HOMOLOG OF BRASSINOSTEROID ENHANCED EXPRESSION2 INTERACTING WITH IBH1 (HBI1) as a negative regulator of PTI signaling in Arabidopsis ( Arabidopsis thaliana ). HBI1 expression is down-regulated in response to different PAMP s. HBI1 overexpression leads to reduced PAMP -triggered responses. This inhibition correlates with reduced steady-state expression of immune marker genes, leading to increased susceptibility to the bacterium Pseudomonas syringae . Overexpression of the HBI1-related bHLH s BRASSINOSTEROID ENHANCED EXPRESSION2 (BEE2) and CRYPTOCHROME-INTERACTING bHLH (CIB1) partially inhibits immunity, indicating that BEE2 and CIB1 may act redundantly with HBI1. In contrast to its expression pattern upon PAMP treatment, HBI1 expression is enhanced by BR treatment. Also, HBI1 -overexpressing plants are hyperresponsive to BR and more resistant to the BR biosynthetic inhibitor brassinazole. HBI1 is nucleus localized, and a mutation in a conserved leucine residue within the first helix of the protein interaction domain impairs its function in BR signaling. Interestingly, HBI1 interacts with several inhibitory atypical bHLH s, which likely keep HBI1 under negative control. Hence, HBI1 is a positive regulator of BR -triggered responses, and the negative effect of PTI is likely due to the antagonism between BR and PTI signaling. This study identifies a novel component involved in the complex tradeoff between innate immunity and BR -regulated growth.